Radiofrequency surgery of the soft palate in the treatment of snoring - a review of the literature - Stuck, Boris; Maurer, Joachim T.; Hein, Gerhard; Hörmann, Karl; Verse, Thomas (Sleep, 2004)
Radiofrequency surgery of the soft palate presents a promising alternative for the treatment of snoring. The aim of this study was to give an overview of the current literature and to quantify the results in terms of a meta-analysis of treatment efficacy.Current databases were searched for publications concerning the treatment of snoring with radiofrequency surgery up to January 2003. Only original articles published in peer-reviewed journals were taken into consideration.The review is based on 22 publications, mostly consisting of prospective noncontrolled clinical trials. Snoring was assessed with the help of visual analogue scales or snoring scores provided by the bed partner. In all these trials, a significant reduction of snoring was reported. Postoperative morbidity was low, but complication rates differed substantially.According to all of the published material, radiofrequency surgery of the soft palate leads to a significant reduction of subjective snoring, and snoring is reduced to a tolerable level. Nevertheless, these findings will have to be confirmed by controlled clinical trials.
Gesehen am 08.04.2022